Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/aem.00888-12
|View full text |Cite|
|
Sign up to set email alerts
|

Distance-Decay Relationships Partially Determine Diversity Patterns of Phyllosphere Bacteria on Tamrix Trees across the Sonoran Desert

Abstract: c Dispersal limitation in phyllosphere communities was measured on the leaf surfaces of salt-excreting Tamarix trees, which offer unique, discrete habitats for microbial assemblages. We employed 16S rRNA gene pyrosequencing to measure bacterial community dissimilarity on leaves of spatially dispersed Tamarix specimens in sites with uniform climatic conditions across the Sonoran Desert in the Southwestern United States. Our analyses revealed diverse bacterial communities with four dominant phyla that exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 36 publications
6
72
1
Order By: Relevance
“…Growth at 28°C was observed on solid media over the range of 2.5 to 150 g of NaCl liter Ϫ1 , similar to that reported for other Halomonas strains (9). In addition, growth was observed up to 41°C, which is above the average maximum temperature bacteria would have been expected to encounter in the arid desert samples (1,20). This indicates that the low relative Halomonas populations observed in arid desert samples were likely caused by factors other than temperature.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Growth at 28°C was observed on solid media over the range of 2.5 to 150 g of NaCl liter Ϫ1 , similar to that reported for other Halomonas strains (9). In addition, growth was observed up to 41°C, which is above the average maximum temperature bacteria would have been expected to encounter in the arid desert samples (1,20). This indicates that the low relative Halomonas populations observed in arid desert samples were likely caused by factors other than temperature.…”
Section: Resultssupporting
confidence: 82%
“…Previous work revealed that while geographical distance represents a significant barrier to bacterial dispersion to Tamarix trees when climatic factors are similar, climatic factors are a major determinant of bacterial community structure on this plant (1,20). The present study has attempted to determine what environmental factors drive the proliferation of Halomonas, a genus exhibiting a strong regional and thus presumably environmental pattern of colonization, on Tamarix trees.…”
Section: Discussionmentioning
confidence: 95%
“…Previous phyllosphere distance-decay studies have found that dispersal limitations are present along with environmental heterogeneity [10,11]. The distribution of abundant taxa, in particular, has suggested that environmental heterogeneity is the likely cause of differences in leaf bacterial communities, while distribution patterns in rare bacterial taxa seemed to support dispersal-driven differences [10].…”
Section: Discussionmentioning
confidence: 97%
“…Compositional differences in the bacterial phyllosphere between different plant species have generally been found to be much greater than intraspecific differences between individuals of the same plant species, even with different geographic origins of the plant host [9]. Conversely, however, geographic location has been found to be a greater predictor of phyllosphere community composition than plant host species and environmental factors [10,11].…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, a study measuring bacterial colonization across initially identical sterile microcosms along a 497 m woodland transect found evidence of dispersal limitation over short timescales (a few days) but also demonstrated that such limitation was not important in shaping community composition 5 over longer timescales (more than a week), at which point the local environment became the more important explanatory variable (Bell 2010). In addition, research characterizing the distance-decay relationship among bacterial colonists of the leaf surfaces of saltexcreting Tamarix trees along a 500-km transect found a strong signature of geographic distance in shaping community composition, but also evidence that salinity and humidity 10 were important environmental factors in explaining community dissimilarity (Finkel et al 2012), emphasizing that the spatial scale at which adaptation is occurring is defined both by spatial distance and by the spatial heterogeneity of selection across the landscape.…”
Section: Bacterial Biogeographymentioning
confidence: 98%